Development of samarium-doped microspheres for internal radiotherapy treatment of bone metastases - Arjuna, Andi (2025)
Internal radiotherapy, also known as brachytherapy, and or selective internal radiotherapy (SIRT), delivers radioactive sources inside the body, near to or into malignant tumours, which may be particularly effective when malignancies are not responding to external beam radiotherapy. 90Y is currently used for internal radiotherapy and commercially available products approved by the FDA. However, the 90Y contained in these yttrium-doped microspheres are pure beta emitters only, which generally needs additional radioactive 99mTc (technetium) for dose calculation and cancer detection in pre-treatments and for dose monitoring and distribution in post treatments.